Dėl pr. -ing- priegaidės - Rinkevičius, Vytautas (Baltistica, 2009)
ON THE SYLLABLE INTONATION OF OPR. -ing- The difference in syllable intonation between the circumflex of OPr. -īng- and the acute of Lith. -ìng-, Latv. -îg- could be explained by the fact that these suffixes acquired stress relatively recently in the separate languages. In Lithuanian it became stressed as a result of Saussure-Fortunatov’s law, i.e. in the period when syllable intonations were distinguished in both stressed and unstressed syllables, whereas the stress of OPr. -īng- might be posterior to a possible neutralisation of syllable intonations in unstressed syllables. Alternatively, at least some of the attested OPr. examples with -īng- can be interpreted as contracted from forms with -īwing-, cf. wertīngs : wertīwings.